The economic impact of the NPL coverage expectations in the euro area - Katarzyna Budnik; Ivan Dimitrov; Johannes Groß; Piotr Kusmierczyk; Max Lampe; Gianluca Vagliano; Matjaz Volk (European Central Bank (ECB), 2022)
This paper looks at the macroeconomic impact of the two policies proposed by ECB Banking Supervision to tackle the high share of non-performing loans (NPLs) on the balance sheets of euro area banks. The first is the coverage expectations for new NPLs set out in the Addendum to the ECB's NPL Guidance, which aim to prevent the build-up of new NPLs, and the second is the coverage expectations for legacy NPLs, which target the reduction of already existing stocks of NPLs. The impact assessment of the package is analysed via a semi-structural model, the Banking Euro Area Stress Test (BEAST). The coverage expectations for NPLs are found to be effective in reducing banks' NPLs. The phase-in of the policies can temporarily reduce bank profitability owing to increased loan loss provisioning targets. However, over a longer time horizon, lower NPL ratios reduce uncertainty and enable banks to access cheaper funding in the markets, ultimately benefiting lending and output growth. Furthermore, the coverage expectations can also moderately but persistently reduce procyclicality in the banking system.
Keywords: E37; E58; G21; G28; 330; Non-performing loans; impact assessment; loan loss provisions; regulatory policy; banking sector; real-financial feedback mechanism; bankingsupervision